2021
DOI: 10.3390/molecules26030734
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Interdigitated Electrode-Based Disposable Enzyme Sensor Strip for Glycated Albumin Measurement

Abstract: Glycated albumin (GA) is an important glycemic control marker for diabetes mellitus. This study aimed to develop a highly sensitive disposable enzyme sensor strip for GA measurement by using an interdigitated electrode (IDE) as an electrode platform. The superior characteristics of IDE were demonstrated using one microelectrode of the IDE pair as the working electrode (WE) and the other as the counter electrode, and by measuring ferrocyanide/ferricyanide redox couple. The oxidation current was immediately reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Here, it can be applied, for example, for cell separation upon biopsy or stem cell culture—( Figure 6 ). The use of this method to create label-free biosensors has already been explored, for example against infections such as dengue or Zika [ 120 ] but more notably for glucose or albumin monitoring [ 121 , 122 ]. Recently, Yoo et al (2021) [ 123 ] described an interdigitated electrode biosensor based on plasma deposited TiO 2 nanoparticles for detecting DNA.…”
Section: Novel In Vitro Models–microfluidic Technologies Applications...mentioning
confidence: 99%
“…Here, it can be applied, for example, for cell separation upon biopsy or stem cell culture—( Figure 6 ). The use of this method to create label-free biosensors has already been explored, for example against infections such as dengue or Zika [ 120 ] but more notably for glucose or albumin monitoring [ 121 , 122 ]. Recently, Yoo et al (2021) [ 123 ] described an interdigitated electrode biosensor based on plasma deposited TiO 2 nanoparticles for detecting DNA.…”
Section: Novel In Vitro Models–microfluidic Technologies Applications...mentioning
confidence: 99%
“…[38] Hatada et al fabricated two GA biosensors using SPCE and interdigitated electrode (IDE) to detect Z-FK, a synthetic analog of e-FK released when GA is digested by protease. [61,66] However, this indirect sensing mechanism does not allow for precise quantification of GA across individuals. Various other studies have reported direct biosensors direct detection of GA, however their response range was outside the clinical relevant range for diabetes and also provided higher LOD than here.…”
Section: Chronoamperometric Deposition Of Au Nps Is Done Bymentioning
confidence: 99%
“…To retrieve an electrical signal, an electron mediator is used: a ruthenium complex (hexaammineruthenium(III) chloride) accepts the electrons involved in the oxidation of -FK, and is simultaneously reduced; then, by applying an oxidative potential to the counter electrode of the sensor, the mediator is oxidized back and the electrons collected at the working electrode generate a current that can be related to the concentration of -FK present in the sample. In 2021, the same authors [ 99 ] modified the design of their biosensor by substituting the SPCE with an IDE, which highly ameliorated the sensitivity and reproducibility of the measurement by providing a higher magnitude of current and further reducing the time needed to reach a steady-state condition, which occurred almost instantaneously. The LOD for the synthetic version of the -FK (i.e., Z-FK) dropped from 40 M to 1.2 M and the sensitivity, previously 0.49 nA/ M, reached 2.8 nA/ M. Figure 3 provides a schematic representation of the electrochemical enzymatic analysis of GA.…”
Section: Glycated Albumin Analysismentioning
confidence: 99%